The Role of Cone Beam Computed Tomographic (CBCT) in Odontology Forensic for Forensic Identification - Fauziah, Yessy Andriani (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 14 No 2 (2024): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2024.v14.i02.p02, 2025)
Cone Beam Computed Tomography (CBCT) is a significant technological advancement in maxillofacial imaging, providing a three-dimensional radiograph that can display the anatomical structure of the jaw bone and face in axial cut or view coronal and sagittal. The main advantage of this technique is that it is a non-invasive method without jaw resection as we have only one scan to be compared with several types of radiographs including panoramic, periapical, and lateral cephalometry. CBCT is popular in dentistry and is increasingly used in forensic cases due to its advantages for antemortem and post-mortem data, including good resolution, portability, and simplicity. CBCT radiography is an important part of forensic odontology because it can support the process of forensic identification of both living and dead through a comparison of antemortem and postmortem data. The use of CBCT radiography is not only for individual identification, but it can also be used to determine the cause of death and predict age, gender, and even ethnic groups. CBCT can also be used as evidence acceptable in the justice system, making it important in forensic identification and medicolegal cases. This current review is an overview of the role of CBCT in odontology forensics especially for identification forensics.